1998
DOI: 10.1046/j.1365-2796.1998.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between aldosterone synthase gene polymorphism and the adrenocortical function in males

Abstract: Polymorphisms in or near the aldosterone synthase gene are associated with variations in aldosterone and 11-deoxycortisol production in males. This may modulate the activity of the renin-angiotensin system and thereby contribute to blood pressure regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
4
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 19 publications
8
56
4
1
Order By: Relevance
“…In keeping with the results of earlier studies, the associations of the CYP11B2 C-344T polymorphism with BP remain inconclusive. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition, our results were not consistent with previous reports indicating that BP elevation was sensitive in elderly subjects with the TT genotype. 20,21 Furthermore, we suggested that the association of the CC genotype with CRP was consistent with previous reports describing the association of the genotype with cardiac structures and atherosclerosis as discussed above, 17,34 whereas some apparent contradictory associations between the genotype and atherosclerosis, including cardiac structure and coronary artery diseases, have been shown in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In keeping with the results of earlier studies, the associations of the CYP11B2 C-344T polymorphism with BP remain inconclusive. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In addition, our results were not consistent with previous reports indicating that BP elevation was sensitive in elderly subjects with the TT genotype. 20,21 Furthermore, we suggested that the association of the CC genotype with CRP was consistent with previous reports describing the association of the genotype with cardiac structures and atherosclerosis as discussed above, 17,34 whereas some apparent contradictory associations between the genotype and atherosclerosis, including cardiac structure and coronary artery diseases, have been shown in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…1,2 One of the polymorphisms of aldosterone synthase (CYP11B2), rs1799998, which is located À344 bp upstream and consistent with either T or C, may influence the cardiovascular system through the effects of aldosterone, because the C allele binds to the steroidogenic factor-1 (SF-1) site five times stronger than does the T allele. 3 An overview of published studies suggests a higher frequency of hypertension or increase in blood pressure (BP) in subjects with the T allele or TT genotype as compared with that in subjects with the C allele or CC genotype, [4][5][6][7][8][9][10] although several studies have reported the opposite association 11,12 or the absence of any association. [13][14][15][16][17][18][19] Thus, the associations remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…8 The mechanism of the association is not known, but may involve an effect of genotype on the activity of the CYP11B2 gene and consequent differences between genotypes on plasma and tissue aldosterone activity. However, the data relating CYP11B2 variants and plasma or urine aldosterone levels are conflicting, with some observing opposite effects of the T-344C polymorphism, 5,27,28 while others have found no effect. 10 Thus, the mechanism of the association between variants at the CYP11B2 locus and anatomical measures of cardiac size remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone synthase genotypes and fasting glucose levels by ethnicity, geographical origin, medication status, and within siblingships gene in in vitro experiments (25). This SNP was associated also with plasma and urinary aldosterone levels (26)(27)(28)(29)(30). Linkage disequilibrium between the T-344C and Lys-173͞Arg SNPs, however, was not examined in these studies, therefore raising the possibility that, in fact, the Lys-173͞Arg SNP (or another undetected polymorphism in this gene) was causatively associated with differences in aldosterone levels in these studies.…”
Section: Discussionmentioning
confidence: 90%